2022
DOI: 10.3390/ph16010060
|View full text |Cite
|
Sign up to set email alerts
|

Nano Methotrexate versus Methotrexate in Targeting Rheumatoid Arthritis

Abstract: Nanomedicine has emerged as an important approach for targeting RA medication. Rheumatoid arthritis (RA) is a widespread autoimmune disorder marked by multiple inflamed joints. Gold nanoparticles (GNPs) have been demonstrated as efficacious nanocarriers due to their unique characteristics and the relative simplicity of their synthesis in varied sizes; moreover, they have the capability to alleviate several inflammatory markers. The current objective was to combine methotrexate (MTX) with GNPs to overcome MTX r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Materials MTX (Methotrexate) was acquired from Sigma (USA). PAMAM dendrimer G3.0 was synthesised at the Institute for Applied Materials Science following the described method [10,11]. Fucoidan (Fu) was purchased from Vietnam (Vietnam Fucoidan Joint Stock Company) [32].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Materials MTX (Methotrexate) was acquired from Sigma (USA). PAMAM dendrimer G3.0 was synthesised at the Institute for Applied Materials Science following the described method [10,11]. Fucoidan (Fu) was purchased from Vietnam (Vietnam Fucoidan Joint Stock Company) [32].…”
Section: Methodsmentioning
confidence: 99%
“…These innovative delivery systems have demonstrated promising potential in improving the management of RA [6][7][8][9]. Among these advancements, various polymeric platforms have been extensively explored and engineered with precisely designed structures to enhance drug loading efficiency [10,11]. Nano-drug delivery systems play crucial roles in improving the effectiveness of treatment and reducing side effects of hydrophobic drugs.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed a marked improvement in the anti-arthritic effects of MTX when it was conjugated with GNPs. Furthermore, histological investigation supported these observations [5]. The aim of the third study was to study the IFN-regulated sialic-acid-binding Ig-like lectin 1 (SIGLEC-1) protein as a biomarker of disease phenotype, therapeutic response, and differential diagnosis in systemic sclerosis (SSc).…”
mentioning
confidence: 88%